Clarifying the Ethics and Oversight of Chimeric Research. (9th December 2022) - Johnston, Josephine; Hyun, Insoo; Neuhaus, Carolyn P.; Maschke, Karen J.; Marshall, Patricia; Craig, Kaitlynn P.; Matthews, Margaret M.; Drolet, Kara; Greely, Henry T.; Hill, Lori R.; Hinterberger, Amy; Hurley, Elisa A.; et al.
Abstract: This article is the lead piece in a special report that presents the results of a bioethical investigation into chimeric research, which involves the insertion of human cells into nonhuman animals and nonhuman animal embryos, including into their brains. Rapid scientific developments in this field may advance knowledge and could lead to new therapies for humans. They also reveal the conceptual, ethical, and procedural limitations of existing ethics guidance for human‐nonhuman chimeric research . Led by bioethics researchers working closely with an interdisciplinary work group, the investigation focused on generating conceptual clarity and identifying improvements to governance approaches, with the goal of helping scholars, funders, scientists, institutional leaders, and oversight bodies (embryonic stem cell research oversight [ESCRO] committees and institutional animal care and use committees [IACUCs]) deliver principled and trustworthy oversight of this area of science. The article, which focuses on human‐nonhuman animal chimeric research that is stem cell based, identifies key ethical issues in and offers ten recommendations regarding the ethics and oversight of this research. Turning from bioethics' previous focus on human‐centered questions about the ethics of "humanization" and this research's potential impact on concepts like human dignity, this article emphasizes the importance of nonhuman animal welfare concerns in chimeric research and argues for less‐siloed governance and oversight and more‐comprehensive public communication .